PENGARUH INFORMASI AKUNTANSI DAN INFORMASI NON AKUNTANSI TERHADAP KEPUTUSAN PEMBERIAN KREDIT DENGAN PENGALAMAN SEBAGAI VARIABEL MODERATING PADA BANK SWASTA KOTA BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
The purpose of this study was to analyze the effect of accounting information and non accounting information on the decision credit with experience as a moderating variables in Private Banking at Batam City. The population used in this study are all the companies applied for credit application in 2014 amounted to 200 debtors. The research sample was taken by using purposive sampling method resulting in 136 companies. The method of analysis used is multiple linear regression analysis with residual test. The first hypothesis simultaneously shows all the independent variables affect on the decision of credit with significant value. While only partial of current ratio, cash ratio, debt to equity ratio, time interest earned ratio, accounts receivable turnover, profit margin, and business reputation variables that influence the decision of credit. Inventory turnover, assets turnover, credit guarantee, debtor education, and business diversification did not affect on the decision of credit. Testing the second hypothesis showed that the existence of experience as a moderating variables have a significant effect on time interest earned ratio variables thus further strengthening their relationship with the decision of credit. However, no significant effect on current ratio, cash ratio, debt to equity ratio, accounts receivable turnover, inventory turnover, assets turnover, profit margin, credit guarantee, business reputation, debtor education, and business diversification variables thus further weakened their relationship with the decision of credit.